Սոցիալական կապիտալի էությունն ու առանձնահատկությունները - Նաիրա Վարդանյան (ՀՀ ԳԱԱ հրատ.)
The term "the social capital" has got wide popularity in the end of the XX-th century. The essence of the concept of the social capital consists that the involvement of the individual into social networks helps it to reach the purposes is easier and faster.
Keywords: Political Science